Caracterização e secagem de grãos de linhaça marrom (Linum usitatissimum L.) em leito fixo e fluidizado - Vieira, Gustavo Nakamura Alves (2012)
Flax (Linum usitatissimum L.) is a plant whose seeds have a high nutritional value due to the presence of polyunsaturated fats and dietary fiber. In terms of health benefits and versatility, flaxseed provides good control of LDL and glycaemic blood levels. In addition, flaxseeds are rich in antioxidants, which prevent degenerative diseases, such as cancer. Flaxseed has featured recently in consequence of the search of foods with functional properties. Although the Brazilian market for flaxseed is growing, it is still dependent on importing, but the potential for the growth of the national production exists, which is a motivation for the research of drying techniques, in such a way that the flaxseed properties between the harvest and the consumption are kept. In order to modeling the drying, some physical properties (amongst which the thermal conductivity, thermal capacity, grain and bulk density and effective mass diffusivity) are required for the use of conservation laws. Generally the relationship of these properties and the moisture of the grains are obtained through rehydration by directly adding water to the grains. However, this procedure does not guarantee the uniformity of the sample. The aim of this study was the proposal of a new methodology to obtain the relation between some physical properties and the moisture of the grains, based on the equilibrium moisture content procedure. Another aim of this study is the analysis of the drying focusing the comprehension of the transport phenomena involved. The equipment used for the drying experiments was a dryer which can be operated either as a batch or a continuous dryer, in fixed or fluidized bed. The influence of drying parameters (air temperature, static bed height and air flow rate) over drying kinetics was analyzed. Results show that the new methodology is potentially applicable to grains and other hygroscopic material. Drying results evidenced that the thin layer thickness for flaxseed at 50°C is between 3 and 5 cm, whereas for higher temperatures (65°C and 80°C), the thickness is equal or above 5 cm. Simple kinetic models (Lewis, Page, Overhults, diffusive) were fit to drying experimental data and the Overhults model was chosen as the most appropriate one to represent the grains moisture as a function of drying time for all the analyzed experimental conditions.